2007
DOI: 10.1111/j.1365-313x.2007.03323.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis her1 mutant implicates GABA in E‐2‐hexenal responsiveness

Abstract: SummaryWhen wounded or attacked by herbivores or pathogens, plants produce a blend of six-carbon alcohols, aldehydes and esters, known as C6-volatiles. Undamaged plants, when exposed to C6-volatiles, respond by inducing defense-related genes and secondary metabolites, suggesting that C6-volatiles can act as signaling molecules regulating plant defense responses. However, to date, the molecular mechanisms by which plants perceive and respond to these volatiles are unknown. To elucidate such mechanisms, we decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 93 publications
7
93
0
Order By: Relevance
“…For example, changes may occur in cellular electrical potential or Ca 21 flux across cell membranes, as has been shown for physical damage (Maffei et al, 2007). Although such ephemeral signals by themselves are unlikely to maintain a primed state, the recent work in Arabidopsis linking g-amino butyric acid with responsiveness to E-2-hexenal provides an intriguing signaling cascade mechanism because wound-induced accumulation of g-amino butyric acid is regulated by the activity of a Ca 21 /calmodulin-dependent Glu decarboxylase (Mirabella et al, 2008).…”
Section: Mechanisms Of Defense Primingmentioning
confidence: 98%
“…For example, changes may occur in cellular electrical potential or Ca 21 flux across cell membranes, as has been shown for physical damage (Maffei et al, 2007). Although such ephemeral signals by themselves are unlikely to maintain a primed state, the recent work in Arabidopsis linking g-amino butyric acid with responsiveness to E-2-hexenal provides an intriguing signaling cascade mechanism because wound-induced accumulation of g-amino butyric acid is regulated by the activity of a Ca 21 /calmodulin-dependent Glu decarboxylase (Mirabella et al, 2008).…”
Section: Mechanisms Of Defense Primingmentioning
confidence: 98%
“…Which VOCs, then, were responsible for the responses that we observed? Green-leaf volatiles have repeatedly been reported to be active in airborne induction of herbivore resistance (Engelberth et al, 2004;Farag et al, 2005;Ruther and Kleier, 2005;Mirabella et al, 2008), and they can also enhance a plant's direct resistance to certain pathogens, particularly necrotrophic fungi (Kishimoto et al, 2005;Matsui, 2006;Shiojiri et al, 2006). Certain volatiles even might be involved in the resistance of plants to abiotic stress (Behnke et al, 2007), and BTH treatment has been reported to enhance the attractiveness of herbivore-damaged corn seedlings to parasitic wasps (Rostás and Turlings, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Described concentrations of volatiles seedlings. 23 In plant lines that are mutant for γ-amino butylic acid (GABA) transaminase, (E)-2-hexenal-dependent growth inhibition was impaired and GABA accumulation was observed. 22 Besides these biological and physiological effects, natural plant aldehydes including (E)-2-hexenal were identified as natural insecticides against stored-product beetles in fumigation tests with wheat grains.…”
Section: Methodsmentioning
confidence: 99%